Exploring the Philosophy of the Local Wisdom of “Gusjigang” for Understanding Zakat and Tax Compliance (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
Zakat and tax play a crucial role in fostering the development of a country. Zakat is an obligation for Muslims, while tax is an obligation for all citizens. Therefore, this research aims to explore the prevailing local wisdom in the Kudus community, in order to gain insights into how these obligations are observed and complied with. The local wisdom philosophy of the Kudus community, known as ‘Gusjigang’, originated from the esteemed heritage of Holy Sunan. It embodies the values of good behavior, studiousness, and tenacious trading (entrepreneurship). Grounded by this philosophy, this study aims to comprehend the motivations behind the adherence of local entrepreneurs to zakat and tax using a case study approach. Following this, in order to gather relevant data, qualitative open-ended interviews and document analysis were employed as the primary source of data collection. Through this process, it was found that the prioritization of zakat over tax stems from the religious regulations and laws, which  take precedence over the mandates of fellow human beings. It is also important to note that from the perspective of the zakat administration, the distribution of zakat was considered more transparent and fairer as evidenced by the insights gleaned from the interviews.